Factors affecting superovulation induction in goats (Capra hericus): An analysis of various approaches - Khan, Samiullah; Jamal, Muhammad Ameen; Khan, Ibrar Muhammad; Ullah, Irfan; Jabbar, Abdul; Khan, Nazir Muhammad; Liu, Yong (Frontiers in Veterinary Science, 2023)
A goat is generally called the “poor man’s cow” which not only provides meat and milk, but also other assistance to the owner, including skins for leather production, and compost for fertilizer. Multiple ovulation and embryo transfer (MOET) is an important process in embryo biotechnology because it increases the contribution of superior females to breeding operations. The field of assisted reproductive biotechnologies has advanced significantly. However, unlike cattle, superovulation and other reproductive biotechnologies have not been widely adopted as standard procedures in goats. Multiple intrinsic and extrinsic factors can alter the superovulatory response, significantly restricting the practicability of MOET technology. Techniques inducing superovulation are used as a mandatory step in embryo transfer (ET) to expedite the propagation of animals with genetic merit for desirable traits. Furthermore, the conventional superovulation techniques based on numerous injections are unpleasant to the animal, labor difficult, and expensive. Different approaches and alternatives have been applied to get the maximum ovarian response including immunization against inhibin, and day 0 protocol for the synchronization of first follicular wave. Unlike cattle, the simplified superovulation in goat are not well studied but only a few studies in the literature are available. In this review, the various treatments of gonadotropin that are used for inducing superovulation among different dairy goat breeds worldwide and their outcome in terms of ovulation rate and recovery of transferrable embryos are described. Furthermore, the recovery of oocytes by repeated superovulation from the same female goat used for Somatic Cell Nuclear Transfer (SCNT), are also reviewed.